Electrochemical impedance spectroscopy study of CuO and Cu coating systems. Issue 6 (3rd November 2014) - Mat Nor, N.A.; Ismail, L.; Jamari, S.K.M.; Ramesh, K.; Vengadaesvaran, B.; Arof, A.K.
Abstract : Purpose: This paper aims to analyse the coating behaviour in corrosion environment as well as to evaluate the best percentage amount of copper oxide and copper needed for organic coating in order to prevent the corrosion degradation. Electrochemical impedance spectroscopy (EIS) studies have been conducted in order to evaluate the corrosion performance of polyester-epoxy-copper oxide and polyester-epoxy-copper coating systems. Design/methodology/approach: The availability of this modem instruments is used to obtain impedance data as well as computer programs to interpret the results that made the technique popular. In addition, EIS is well suited to the study of polymer-coated metals. Findings: The results showed that samples containing 25 weight per cent of copper oxide and copper (90P25CuO and 90P25Cu) obtained the excellent corrosion properties from the first day up to 30 days of NaCl immersion. The highest corrosion resistance values obtained by 90P25CuO and 90P25Cu on the 30th day were 7.107 × 108 O and 5.701 × 108 O, respectively, with lower double layer capacitance of 1.407 × 10 −9 Farad and 3.935 × 10 −9 Farad, respectively. Moreover, the water uptake gained by these two coating samples was the lowest at the end of immersion, which was 0.0084 for 90P25CuO and 0.1592 for 90P25Cu, showing that the sample has good corrosion performance. Originality/value: This paper discussed on the highest corrosion resistance, double layer capacitance and the water uptake of the copper (Cu) and copper oxide (CuO) coating system obtained from the EIS measurements.